Segmentation of River Networks from Multispectral Remote Sensing Data Using Deep Neural Networks - Souza, Eduardo H. P.; Boldt, Francisco de A.; Paixão, Thiago M.; Andrade, Jefferson O.; Komati, Karin S. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2026.248616, 2026)
Research Context: Accurate hydrological mapping is essential for water resource management, flow modeling, and risk assessment of flooding and erosion. Scientific Problem: Conventional methods and RGB satellite imagery fail to map watercourses obscured by dense vegetation, resulting in fragmented, unreliable cartography that compromises territorial planning. Proposed Solution: We propose a comparative analysis of river network semantic segmentation, evaluating U-Net and DeepLabv3+ architectures with ImageNet pre-trained backbones (EfficientNet-B5, ResNet-152). The analysis utilizes multispectral data (RGB, NIR) and spectral indices (NDWI, NDVI, GNDVI) to enhance feature discrimination. Related IS Theory: This work aligns with TaskTechnology Fit by evaluating the suitability of deep learning for automated river network extraction. Research Method: We created a dataset from satellite imagery and official vector data of two Brazilian basins (Doce, Itapemirim). Models were trained in intra-dataset, combined, and cross-dataset scenarios using mean Intersection over Union (mIoU). Summary of Results: For intra-dataset evaluation, U-Net using EfficientNet-B5 yielded 84.86±0.39% mIoU, whereas DeepLabv3+ with ResNet-152 showed 86.73±0.21%. Combined datasets provided stable metrics (82.25±0.51% for U-Net). Cross-dataset tests reached 63.96% mIoU, indicating a performance decrease. Contributions/Impact: This study demonstrates that U-Net and DeepLabv3+ architectures using deep backbones accurately segment river networks in complex environments. The methodology provides a viable approach to automate drainage network extraction, supporting environmental management and hydrological modeling.